Sintomas depressivos e níveis plasmáticos do fator neurotrófico derivado do cérebro em idosos da comunidade - Aroca, Graciele Guimarães Pitelli (2018)
The increase of lifespan in elderly population leads to a growth in prevalence and incidence of chronic-degenerative disease. It compromises the independence and autonomy of the elderly adults individuals. The depression is a common psychiatric disorder in the elderly population and it may cause suffering and aggravation of pre-existing diseases. On this context, the reduction of Brain Derived Neurotrophic Factor (BDNF) in plasmatic levels has been associated to depression itself and depressive symptoms. However, in the elderly population it is a controversy, due to the scarcity of research on Brazilian population. Objective: Investigate the association between depressive symptoms and plasmatic levels of BDNF in older residents from community, related to Family Health Strategy at the city of Alfenas/MG in Brazil. Methodology: It is a cross-sectional, population-based observational. The sample was composed by 496 elderly adults above 60 years, considering women and men. In order to characterize the sample, it was collected sociodemographic and clinical data. The presence of depressive symptoms was identified by Geriatric Depression Scale (GDS). The dosage of plasmatic levels of BDNF was evaluated by Elisa method, kit DuoSet (R&D Systems, Minnesota, MN). The association between depressive symptoms and plasmatic levels of BDNF was analyzed by the binomial logistic regression, even after correcting for other confounding parameters: age, sex, marital status, education, comorbidities, medicaments and physical activity. In all analysis, it was considered an α=5%. In addition, the SPSS software to Windows (Versão 20.0) was used. Results: The frequency of SDCS was 18,7%. Elderly wich SDCS presented higher plasmatic levels of BDNF. On the other hand, the dosages of that neurotrophin was not associated to depressive symptoms in the sample. The number of comorbidities, education and physical activity were the factors which influenced on depressive symptoms. Moreover, education and physical activity have a protective effect on those symptoms. Conclusion: in present study, the levels of BDNF were not associated to depressive symptoms in elderly adults in the community. The variables that influenced the depressive symptom were the number of comorbidities, education and physical activity, which the lasts two caused a protect effect.